RANCANG BANGUN SISTEM VERIFIKASI DATA DOKUMEN - Putra Pamungkas, Danar (Inovate, 2019)
A Study Program certainly has a routine agenda every semester, such as a thesis session. Before the trialthesis is carried out, there are several stages that are passed. The recap and data verification phase is donemanually by the study program admin by looking at the complete requirements file. The process arises aproblem that is unable to know the authenticity of the requirements documents, especially the guidancesheet file, the approval of the trial registration from the lecturer. So we need a system that can solves theseproblems. The system will be created using the Two Factor Authentication (2FA) method because theverification process is not enough to do with a username and password. Using the 2FA method theverification system can ensure that the person who verifies is the authority. The result is an informationsystem for document management and document verification has been made using the Two FactorAuthentication (2FA) method..Keywords: document, verification, 2FA